Stem cells and cancer stem cells, volume 7 therapeutic applications in disease and injury - Hayat, M.A (Stem Cells and Cancer Stem Cells, 2012)
This seventh volume in the Springer's landmark series of edited books discusses one of the most important subjects in contemporary medicine and scientific endeavors. The volume presents a staggering range of research into medical applications of stem cells and cancer stem cells. While stem cells are essential for normal life of multicellular organisms, including humans, cancer stem cells are a morbid entity having a robust resistance to therapies including conventional chemotherapy and radiotherapy. This authoritative publication explains the regenerative potential of stem cells and their mesenchymal progeny, reviewing clinical applications of the latter in the treatment of cancer, diabetes and neurodegenerative pathologies. It covers the entire range of stem cells with known potential for therapeutic use, from human embryonic to germ cell-derived pluripotent stem cells and hematopoietic stem cells. The chapters also deal with the role of TGF-beta in propagating human embryonic stem cells, and in facilitating their differentiation. Featuring discussions of molecular signaling pathways that modulate mesenchymal stem cell self-renewal and much more, this book is certain to have broad appeal among academicians and physicians alike.